Cruzar las fronteras: el sujeto itinerante y las migraciones objetivas y subjetivas (El Hilo de la Fabula, 2020)
This article offers some considerations about the dynamics of the borders, from the historical and geographical borders to the perceptive ones. Also, it looks into the centrifugal and centripetal processes that shape the identity of the migrating subject and their perspective in both objective and subjective migration processes. To illustrate these motions, this article offers a literary example of the processes of searching and change in perceptive and transcendent borders by tackling Borges’ tale «La Rosa de Paracelso».
Keywords: Identity; Frontiers; Migrations; Perspectives; Transcendence; Borges; Kabbalah